IMPLEMENTATION OF OPEN CLASS AT FLIPPED CLASSROOM BASED ON INFORMATION TECHNOLOGY IN ISLAMIC STUDIES SUBJECT AT PHARMACY DEPARTMENT UII - Harimurti, Shubhi Mahmashony (PEOPLE: International Journal of Social Sciences, 2019)
Islamic Studies is a main university subject which is also taught at Pharmacy Department. The teaching problem so far is that students when taking lectures are considered not so ready to receive material. They go into class as if they are just carrying out a formality. The worst thing is just being present so that attendance calculations can qualify for the Final Semester Examination. This condition must be changed immediately. The implementation of the Flipped Classroom method aims to make students already have the material to be delivered in class before the lecture begins. Students are expected to be better prepared to follow the learning process. Flipped Classroom innovation is used by optimize the Information Technology (IT). Some applications like social media Youtube and Google Classroom are maximized. The rise of social media among students must be bridged not banned. Youtube is one of the social media favored by students. This learning program also emphasizes student activity. The main purpose of the implementation of this learning is to analyze the most appropriate teaching methods by promoting Student Centered Learning (SCL). Open Class is one of the methodologies that are adopted in this learning. The findings obtained from this model of learning are that students are far more ready to receive lecture material. Because it has been studied before. One way to measure program achievement is to look at student reflective videos related to the themes discussed in class. The researcher can conclude that the application of Open Class can help improve the quality of learning.